Review of Alexis Rappas' Cyprus in the 1930s: British Colonial Rule and the Roots of the Cyprus Conflict - Braat, Eleni (Historein, 2022)
Review of Alexis Rappas, Cyprus in the 1930s: British colonial rule and the roots of the Cyprus conflict, London: IB Tauris, 2014. 320 pp.